STRATEGI KESANTUNAN POSITIF DAN NEGATIF DALAM BENTUK TUTURAN DIREKTIF DI LINGKUNGAN STKIP MUHAMMADIYAH PRINGSEWU LAMPUNG - Saputry, Dessy (JURNAL PESONA, 2016)
In doing communication, polite behaviour is very influence in creating comfortableatmosphere. Polite behaviour can be in the form of verbal and nonverbal. Thisresearch described the positive and negative strategi that related to the unity of theform of direct speech at STKIP Muhammadiyah Pringsewu. This research wassosiopragmatic study with qualitative descriptive approach. The data analysistechnique used in his research was interactive model which was contain of datareduction, data serve, and conclution or verification. Based on the result of theresearch, the politeness strategy in the direct speech which was applied at STKIPMuhammadiyah Pringsewu Lampung were using positive and negative strategy.Based on the analysis result, they were some factors that influenced the positivestrategy happen. They were as follows: kind of attention, the solidarity betweenperson, the feeling of being appreciated and giving appreciation, giving praise,avoiding incompatibality and creating jokes. Meanwhile, the negative strategy wereinfluenced by some factors. They were as follows: indirect speech, pesimistic attitude,reducing coercion, using passive voice, apology, and using plural form. The positiveand negative strategy that happened was the effort to create the politeness in doingcommunication.Key Note: Strategi Kesantunan, tuturan direktif, sosiopragmatik